Hybrid Close-Loop Systems Versus Predictive Low-Glucose Suspend and Sensor-Augmented Pump Therapy in Patients With Type 1 Diabetes: A Single-Center Cohort Study - Lunati, Maria Elena; Morpurgo, Paola Silvia; Rossi, Antonio; Gandolfi, Alessandra; Cogliati, Irene; Bolla, Andrea Mario; Plebani, Laura; Vallone, Luciana; Montefusco, Laura; Pastore, Ida; Cimino, Vincenzo; Argenti, Sabrina; et al. (Frontiers in Endocrinology, 2022)
INTRODUCTION: Predictive low-glucose suspend (PLGS) and hybrid closed loop (HCL) systems may improve glucose control and quality of life in type 1 diabetic individuals. This is a cross-sectional, single center study to compare the effect on metabolic control and glucose variability of PLGS, HCL systems as compared to standard sensor-augmented pump (SAP) therapy. METHODS: We retrospectively analyzed 136 adults (male/female 69/67, mean age 47.3±13.9 years) with T1D on insulin pump therapy, divided accordingly to type of insulin pump system (Group 1: SAP, 24 subjects; Group 2: PLGS, 49 subjects; Group 3: HCL, 63 subjects). The groups were matched for age, gender, years of disease, years of CSII use and CGM wear time. RESULTS: The analysis of CGM metrics, in the three groups, showed a statistically significant different percentage of time within the target range, defined as 70-180 mg/dl, with higher percentage in group 3, and a significant lower time spent in hypoglycemic range in group 2 and 3. The three groups were statistically different also for glucose management indicator and coefficient of variation percentage, that were progressively lower moving from group 1 to group 3. In the HCL group, 52.4% of subjects reached a percentage of time passed in euglycemic range above 70%, as compared to 32.7% in those with PLGS and 20.2% in those with SAP. A positive correlation between higher percentage of TIR and the use of auto-mode was evident in the HCL group. Finally, the three groups did not show any statistically differences regarding quality-of-life questionnaire, but there was a significant negative correlation between CV and perceived CSII-use convenience (r= -0.207, p=0.043). CONCLUSIONS: HCL systems were more effective in improving glucose control and in reducing the risk of hypoglycaemia in patients with type 1 diabetes, thereby mitigating risk for acute and chronic complications and positively affecting diabetes technologies’ acceptance.